2020
DOI: 10.1177/0886260520934443
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Disclosures of Physical Abuse in a Population-Based Sample

Abstract: Few studies have explored the disclosure of child physical abuse although child sexual abuse disclosure has been widely studied and debated for years. The present study explores the characteristics of child physical abuse disclosures and compares them to previously published findings on child sexual abuse disclosure from the same data. The data consist of a representative sample of 11,364 sixth and ninth graders. Participants responded to a wide variety of questions concerning experiences of violence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 47 publications
2
16
0
Order By: Relevance
“…Finally, our results suggest that a segment of young people who seek support from local adults do not receive supportive responses, nor does their situation change. Although our study is not able to evaluate the frequency at which this occurs, other studies suggest negative disclosure experiences are common (Jernbro et al, 2017;Lahtinen et al, 2020;McGuire & London, 2020). Thus, it may also be necessary for our systems that engage with young people, including the child protection system, to examine their current practices.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Finally, our results suggest that a segment of young people who seek support from local adults do not receive supportive responses, nor does their situation change. Although our study is not able to evaluate the frequency at which this occurs, other studies suggest negative disclosure experiences are common (Jernbro et al, 2017;Lahtinen et al, 2020;McGuire & London, 2020). Thus, it may also be necessary for our systems that engage with young people, including the child protection system, to examine their current practices.…”
Section: Discussionmentioning
confidence: 91%
“…Other common reasons for not reporting included being embarrassed, being afraid to get in trouble or upset the abuser, or because they did not want the abuser to get in trouble. A study among Finnish young people found similar reasons for nondisclosure, including perceptions that their experiences were not serious, that disclosure would not result in help, or that others would not be interested in their experiences ( Lahtinen et al, 2020 ). Studies in other locations across multiple decades have found similar perceptions among young people ( Jensen et al, 2005 ; Jernbro et al, 2017 ; Palmer et al, 1999 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, authorities with a duty to report child abuse and intervene are perceived of as the gatekeepers of children’s safety and wellbeing (Ashton, 1999). Yet, child-victim surveys show that only a small fraction of children’s experiences of victimisation are acknowledged by authorities (Bunting, 2014; Lahtinen et al, 2020); hence, highlighting the importance of effective intervention policies and clearly stated responsibilities in this context.…”
Section: Generational Order State Interventions and Invisibilities Of Violence In The Private Spherementioning
confidence: 99%
“…Several studies found that the most common self-reported reason for non-disclosure is that many children considered their experiences of violence not to be serious enough to report. They do not recognize their experiences as abusive or view some of the abusive acts as a normal part of everyday life [ 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%